Analisis Pengaruh Risk Profile Terhadap Profitabilitas Unit Usaha Syariah Pada Tahun 2015 – 2023 - Aryani, Sania Nisa; Setiawan, Iwan (Journal of Applied Islamic Economics and Finance, 2024)
The increase in financing accompanied by a decrease in credit risk in Sharia Business Units does not increase profitability. So this research was conducted to see the effect of risk profile on profitability. Risk profile variables will be proxied by NPF, PSR, FDR, and AC. There are 11 samples of Islamic Business Units that meet the criteria as research objects by taking quarterly report data from 2015 - 2023. Panel Data Regression Analysis is used to analyze and the results show that NPF and AC have a negative effect, FDR has a positive effect and PSR has no effect on ROA. Since AC has the most dominant influence, the Islamic Business Unit should invest cash in short-term securities (more liquid than financing) to avoid idle money.